Hacking the hacker : learn from the experts who take down hackers - Grimes, Roger A. (Wiley, 2017)
Meet the world's top ethical hackers and explore the tools of the trade Hacking the Hacker takes you inside the world of cybersecurity to show you what goes on behind the scenes, and introduces you to the men and women on the front lines of this technological arms race. Twenty-six of the world's top white hat hackers, security researchers, writers, and leaders, describe what they do and why, with each profile preceded by a no-experience-necessary explanation of the relevant technology. Dorothy Denning discusses advanced persistent threats, Martin Hellman describes how he helped invent public key encryption, Bill Cheswick talks about firewalls, Dr. Charlie Miller talks about hacking cars, and other cybersecurity experts from around the world detail the threats, their defenses, and the tools and techniques they use to thwart the most advanced criminals history has ever seen. Light on jargon and heavy on intrigue, this book is designed to be an introduction to the field; final chapters include a guide for parents of young hackers, as well as the Code of Ethical Hacking to help you start your own journey to the top. Cybersecurity is becoming increasingly critical at all levels, from retail businesses all the way up to national security. This book drives to the heart of the field, introducing the people and practices that help keep our world secure.-Go deep into the world of white hat hacking to grasp just how critical cybersecurity is -Read the stories of some of the world's most renowned computer security experts -Learn how hackers do what they do-no technical expertise necessary -Delve into social engineering, cryptography, penetration testing, network attacks, and more As a field, cybersecurity is large and multi-faceted-yet not historically diverse. With a massive demand for qualified professional that is only going to grow, opportunities are endless. Hacking the Hacker shows you why you should give the field a closer look.- Resumé vydavatel
Keywords: hackování; hackeři; počítačová bezpečnost; kybernetická bezpečnost; computer hacking; hackers; computer security; cyber security; elektronické knihy; monografie; electronic books; monographs